Pengaruh Ketinggian Perangkap dan Komposisi Bahan Atraktan Terhadap Serangan Hama Penggerek Buah Kopi - Basri Basri; Nasamsir Nasamsir; Araz Meilin (Universitas Batanghari, 2023)
Coffee berry borer (Hypothenemus hampei) is the main pest on coffee causing significant losses with more than 10% of coffee attacked. This research aims to know the effective height of the trap and composition of the attractant to control liberika tungkal komposit coffee berry borer Betara sub-district, West Tanjung Jabung District, Jambi Province. This research was conducted from August to October 2019 at Terjun Gajah Village by the percentage of coffee attacked 12.32%. The method used Randomized Block Design with two factors and four replications. The first factor was the height the of trap (1,2 m, 1,4 m, 1,6 m, and 1,8 m), and the second factor was the composition of attractant (ethanol : methanol (1:1) + coffee peel extract, ethanol : methanol (1:2) + coffee peel extract, ethanol : methanol (1:3) + coffee peel extract, and control (coffee peel extract only)). The results showed that only the height of the trap was significant by the coffee berry borer trapped. The best trap used ethanol : methanol(1:3) + coffee peel extract at 1,6 m height of trap with the adult of CBB number is 66 individuals.